Advertising on Social Media Influences Purchase Intent: The Role of Mediating Consumer Engagement and Brand Trust - Kadarisman Kadarisman; Erick Karunia; Syahran Syahran; Ahmad Juliana; Muh. Irfandy Azis; Deni Marsha (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
This study aims to analyze the influence of social media advertising on consumer purchase intention, with trust in brands and consumer involvement in MSMEs in Malinau Regency as mediating variables. This study uses a quantitative approach with an explanatory research design. Data were collected by distributing questionnaires to social media users and MSME consumers in Malinau Regency. The study used purposive sampling with 110 respondents. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test relationships among variables in structural models. The variables studied included social media advertising as the independent variable, brand trust and consumer engagement as mediating variables, and purchase intent as the dependent variable. The results show that social media advertising has a positive and significant effect on brand trust, consumer engagement, and purchase intent. Trust in brands has a positive and significant effect on purchase intent, whereas consumer involvement has no significant effect. These findings show that trust in brands is a key factor in increasing consumer purchase intent among MSMEs. The implications of this study emphasize the importance of social media marketing strategies that focus on building brand trust to increase the effectiveness of consumer promotion and purchase decisions. In terms of policies and practices, MSME actors need to optimize the credibility, transparency, and quality of digital communication. Further research is recommended to include additional relevant variables and broaden the research scope to improve the generalizability of the findings.